Optimization on crucial ejector geometries in a multi-evaporator refrigeration system for tropical region refrigerated trucks. (15th December 2019) - Li, Shengyu; Yan, Jia; Liu, Zhan; Yao, Yong; Li, Xianbi; Wen, Na; Zou, Guorong
Abstract: In this paper, a novel ejector-based multi-evaporator refrigeration system using R134a is proposed to meet different working modes of refrigerated trucks running in tropical regions. The Computational Fluid Dynamics (CFD) simulation is implemented to research the performance of ejectors utilized in both air conditioning - refrigerating mode and air conditioning - freezing mode. Consequently, crucial ejector geometrical parameters such as area ratio (AR), nozzle exit position (NXP), lengths of primary nozzle and diffuser are optimized for each mode. Moreover, a novel approach by taking the deviation of the entrainment ratio or secondary mass flow rate over the deviation of the geometrical parameter into account to evaluate the ejector performance sensitivity to each geometrical parameter is first time presented to the best of the authors' knowledge. The results show that: 1) Area ratio, NXP, lengths of primary nozzle and diffuser of the ejector in the air conditioning - freezing mode are almost twice as those in the air conditioning - refrigerating mode; 2) The performance of both ejectors is primarily influenced by area ratio and NXP; 3) The proposed sensitivity indicator can better evaluate the sensitivity of the ejector performance to geometrical parameters. Highlights: A novel ejector-based multi-evaporator refrigeration system is presented. Effect of key ejector geometries of each mode on ejector performance is evaluated. Best ejector performance is obtained by optimizing key ejector dimensions. Optimum ejector geometries are largely dependent on operating mode. A new approach assessing the ejector performance sensitivity is proposed.